A Brief Review on Immunology of Dental Caries and Caries Vaccine - Ghosal, Rhitam; Gayen, Swagata; Mahmud , Sk. Abdul; Das, Sanjeet Kumar; Pal , Mousumi (International Journal of Innovative Research in Medical Science, 2024)
Dental caries is an irreversible microbial disease of the calcified tissues of the teeth, characterized by demineralization of the inorganic portion and destruction of the organic substance of the tooth, which often leads to cavitation. Untreated dental caries in deciduous teeth was the tenth most widespread and the fourth most expensive chronic illness to treat condition among children worldwide, with prevalence peaking at the age of six. Individuals with active caries have an elevated serum antibody level for mutans streptococci. Findings also suggest that an increased antigenic load (bacteria from lesions) will give rise to elevated salivary antibody. Subjects with selective IgA deficiency without salivary antibody show markedly elevated levels of dental caries when compared to normal controls. IgA deficient subjects with IgM compensatory antibodies have significantly less caries than simply IgA deficient subjects. The immune system in secretions have been used to interfere with caries by stimulating salivary antibodies to appropriate antigens. The gingival crevicular fluid contributes IgG, which can also interfere with caries. This review article emphasizes the comprehensive and contemporary idea about immunological aspect of dental caries along with overview on dental caries and immunity and recent advancements in the field of caries vaccine.